2-Alkyl-4-quinolone quorum sensing molecules are biomarkers for culture-independent Pseudomonas aeruginosa burden in adults with cystic fibrosis. Issue 10 (1st October 2021) - Zain, Nur Masirah M.; Webb, Karmel; Stewart, Iain; Halliday, Nigel; Barrett, David A.; Nash, Edward F.; Whitehouse, Joanna L.; Honeybourne, David; Smyth, Alan R.; Forrester, Douglas L.; Knox, Alan J.; Williams, Paul; et al.
Abstract : Introduction. Pseudomonas aeruginosa produces quorum sensing signalling molecules including 2-alkyl-4-quinolones (AQs), which regulate virulence factor production in the cystic fibrosis (CF) airways. Hypothesis/Gap statement. Culture can lead to condition-dependent artefacts which may limit the potential insights and applications of AQs as minimally-invasive biomarkers of bacterial load. Aim. We aimed to use culture-independent methods to explore the correlations between AQ levels and live P. aeruginosa load in adults with CF. Methodology. Seventy-five sputum samples at clinical stability and 48 paired sputum samples obtained at the beginning and end of IV antibiotics for a pulmonary exacerbation in adults with CF were processed using a viable cell separation technique followed by quantitative P. aeruginosa polymerase chain reaction (qPCR). Live P. aeruginosa qPCR load was compared with the concentrations of three AQs (HHQ, NHQ and HQNO) detected in sputum, plasma and urine. Results. At clinical stability and the beginning of IV antibiotics for pulmonary exacerbation, HHQ, NHQ and HQNO measured in sputum, plasma and urine were consistently positively correlated with live P. aeruginosa qPCR load in sputum, compared to culture. Following systemic antibiotics live P. aeruginosa qPCR load decreased significantly ( P <0.001) and was correlated with a reduction in plasma NHQ (plasma: r=0.463, P =0.003). Conclusion. In adults with CF, AQ concentrations correlated more strongly with live P. aeruginosa bacterial load measured by qPCR compared to traditional culture. Prospective studies are required to assess the potential of systemic AQs as biomarkers of P. aeruginosa bacterial burden.